A scoping review of peer mentoring in medicine. (25th June 2022) - Farid, Huma; Bain, Paul; Huang, Grace
Abstract: Background: While studies have demonstrated the benefits of mentoring between junior and senior faculty, the dearth of senior mentors remains a challenge. Peer mentoring arose out of scarcity by creating communities among faculty at similar stages. Although demonstrative studies abound, no synthesis of the literature exists to characterise programme structure, content and impact on faculty. Methods: We conducted a scoping review of peer mentoring programmes for faculty in academic medicine. We searched MEDLINE, Embase, Web of Science and ERIC for studies of peer mentoring programmes. Two authors independently reviewed the articles and extracted data. Findings: We reviewed the titles and abstracts of 1513 studies, 75 full‐text articles, and selected 19 studies for our review. About half of peer mentoring programmes were department‐sponsored. The overall size varied from 3 to 104 participants; most were organised into small groups and met monthly. Fifty‐eight percent included a didactic curriculum. Several studies showed an increase in publications, grant funding, retention rates and promotion, in addition to increased personal satisfaction. Qualitative data demonstrated themes of collaboration and mutual support. Discussion: Programme outcomes were invariably positive with respect to participant satisfaction, and additionally, some studies showed an increase in publications, grant funding, retention rates and promotion. Camaraderie emerged as a strong theme in the programmes. Conclusions: This scoping review of peer mentoring programmes can guide institutions in their efforts to create similar initiatives.